Learning about the circular economy in rural communities of Cauca - Vidal Pinilla, Gehovell J.; Vidal Pinilla, Yanlika A. (Cuadernos de Administración, 2022)
The objective of this article is to reveal the learning about the circular economy from two research experiences in rural communities of the municipalities Cajibío and Popayan in the department of Cauca. For this purpose, the triangulation of information was used from the analysis of secondary sources and information from primary sources obtained through the application of surveys, focus groups and immersions in context. Finally, a contrast analysis was carried out on the results obtained with the theory found that supports the principles of the circular economy. The results tend to generate learning about the circular economy derived from community practices in the use of waste from rural households that can be oriented toward the valorization of benefits to leave behind the traditionally perceived linear economic model to highlight the use of these wastes as resources contributing to reducing pollution levels and increasing income generation options in the rural communities under study.